Another Look At a Feminist Ethics of Teaching - Engelmann, Donna (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
By drawing on feminist epistemology, ethics and pedagogy this paper articulates some aspects of a care-based ethics of teaching. Understanding teaching as a species of caring, it explores some consequences for teaching practice of the attentiveness, responsiveness, and responsibility characteristic of caring professionals.